2018
DOI: 10.1063/1.4997570
|View full text |Cite
|
Sign up to set email alerts
|

The role of geodesic acoustic mode on reducing the turbulent transport in the edge plasma of tokamak

Abstract: Three sets of triple probe arrays (four-tip) are applied to study the transport properties at the edge of a HL-2A tokamak. The Geodesic Acoustic Mode (GAM) exhibits intermittent characteristics during the discharge. The radial particle flux has been studied in different phases corresponding to the variable GAM intensity. The experimental results reveal that the radial particle flux contributed by the ambient turbulence (20 kHz–100 kHz) has been suppressed by 13% during the GAM bursts, contrasting weak GAM case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…In the high-frequency part, i.e. 15-100 kHz, it is found that the fluctuation level in both Ṽf and ñe is significantly increased compared with figures 6(b) and (c), despite the coherence, the phase shift between ñe and Ṽf and the poloidal wave number (k θ ) all being almost unchanged; we conclude that the enhanced particle transport is mainly attributed to the increased power in ñe and Ṽf rather than the phase shift, which is consistent with the previous experimental observations [43]. The amplitude level of GAM zonal flow and local turbulent transport show opposite behaviors, demonstrating that GAM zonal flow is coupled with local particle transport.…”
Section: The Role Played By the Gam Zonal Flow In Regulating Turbulen...supporting
confidence: 91%
“…In the high-frequency part, i.e. 15-100 kHz, it is found that the fluctuation level in both Ṽf and ñe is significantly increased compared with figures 6(b) and (c), despite the coherence, the phase shift between ñe and Ṽf and the poloidal wave number (k θ ) all being almost unchanged; we conclude that the enhanced particle transport is mainly attributed to the increased power in ñe and Ṽf rather than the phase shift, which is consistent with the previous experimental observations [43]. The amplitude level of GAM zonal flow and local turbulent transport show opposite behaviors, demonstrating that GAM zonal flow is coupled with local particle transport.…”
Section: The Role Played By the Gam Zonal Flow In Regulating Turbulen...supporting
confidence: 91%
“…Similarly, in T-10 using HIBP the particle flux associated with an f > 100 kHz QC mode can be seen to in anti-phase with the GAM amplitude [297]. Further, in HL-2A using forked LPs a 13% reduction in Γ r (due to broad-band 20-100 kHz AT) was measured during intermittent bursts of strong GAM activity, as shown in figure 107, compared to periods of weak GAM activity [549]. As with IST-TOK, the Γ r was also found to decrease with increasing GAM strength (measured from Cov(τ = 0) between poloidally separated probe V f ).…”
Section: Particle and Energy Transportmentioning
confidence: 82%
“…As with T-10, the f GAM modulation depth was several kHz. In some devices the modulation can be particularly strong, as in HL-2A where the GAM amplitude modulation approached 100% [549].…”
Section: Gam Modulation and Intermittencymentioning
confidence: 99%
“…19(c), very similar to experimental measures of GAM intermittency. [25,[37][38][39][40][41][42][43][44]…”
Section: Nonlinear Coupling Between Multiple Central Rational Surface...mentioning
confidence: 99%